Social Assistance and Informality: Examining the link in Colombia (2013)
This paper presents evidence on the labor market effects of social assistance programs in the short and medium run. We evaluate the impacts of a Conditional Cash Transfer program (Familias en Acción) on informality in Colombia. We exploit an exogenous shock linked to cash transfer benefits that the government provides to poor people to evaluate the effect of these benefits on informality. We argue that being a beneficiary of social programs may create perverse incentives that drive people towards informality through a substitution effect. Survey data of “Familias en Acción” program was used to identify whether the program had any effect on workers’ labor decisions concerning participation (or the lack thereof) in the informal labor market in Colombia after one and four years after its implementation. We apply matching algorithms and difference-in-differences estimations to evaluate the effect of the program. We find that a worker’s informality condition may be affected by receiving CCT income and by the structure of the colombian health system.